Ease of Practical Information Access in the Digital Transformation Era Through the Utilization of the Earthquake Websitein Kaimana Regency - Erfan Wahyudi; Elias Hendrik Frasawi; Ahmed Shodiq Al Misry (International Journal of Scientific Research, 2024)
This study aims to investigate and analyze the extent to which ease of access to information through the Earthquake Website can enhance the quality and speed of earthquake information dissemination in Kaimana Regency. Using qualitative methods and an analytical descriptive approach, this research provides an in-depth depiction of how users utilize the website, the challenges encountered, and its impact within the context of digital transformation in the region. The findings indicate that the Earthquake Website provides real-time information about earthquake locations, magnitudes, and potential hazards. Collaboration between the government, non-governmental organizations, and the local community strengthens efforts in earthquake disaster prevention and mitigation. However, several challenges hinder the optimal use of this website, such as low digital literacy, limited internet access in remote areas, and a lack of public awareness regarding the importance of the provided information. To address these challenges, proposed solutions include digital literacy education and training programs, enhancement of digital infrastructure, and intensive and continuous awareness campaigns. This research underscores the significance of the Earthquake Website in earthquake mitigation efforts and highlights strategic measures that can be taken to overcome existing obstacles. With the implementation of appropriate solutions, it is expected that the effectiveness of the website's use can be improved, thereby optimizing earthquake prevention and mitigation efforts in Kaimana Regency.